Effect Variation Side Rake Angle and Depth of Cut Shapping Flat to Low Carbon Steel ST-37 Surface Roughness Value - Muhammad Ichsan; Yufrizal A; Refdinal Refdinal; Rifelino Rifelino (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
The product quality of the production process using such production machine is always associated with dimensional precision, tolerance, and surface roughness. It is difficult to obtain the surface quality of the desired workpiece and yet to be aware of the precise parameters of the chisel eye angle, so that when the surface quality flat suction is not fixed and not as desired Problems in this study. The purpose of the study is to determine the influence of one of the different eye angle variations of the chisel, the Side Rake Angle and the depth of the cut to the small surface roughness value in the workpiece of flat shapping. The method used in this research is the experimental method. The results showed, from nine times the test gained two good tests on the roughness of the ST-37 steel material the first test of variation side rake angle 14 ⁰ at a depth of cut 0.5 mm as many as 3 specimens with a total surface roughness value of three specimens of 3.35 μm and the fourth Test was with a variation of side rake angle 16 ⁰ at a depth of 0.5 mm as many as 3 specimens with a total roughness value of 3.47 μm and a roughness value Each specimen in class N8. Kualitas produk dari proses produksi yang menggunakan mesin-mesin perkakas produksi selalu dikaitkan dengan ketepatan dimensi, toleransi, dan kekasaran permukaan. Sulitnya untuk mendapatkan kualitas permukaan benda kerja yang di inginkan serta belum diketahuinya parameter sudut mata pahat yang tepat menjadi masalah dalam penelitian ini. Tujuan penelitian adalah untuk mengetahui pengaruh salah satu variasi sudut mata pahat yaitu Side Rake Angle dan kedalaman pemotongan terhadap nilai kekasaran permukaan yang kecil pada benda kerja hasil penyekrapan datar. Metode yang digunakan dalam penelitian ini adalah metode eksperimen. Hasil penelitian menunjukan, dari Sembilan kali pengujian didapat dua pengujian yang bagus terhadap kekasaran bahan baja ST-37 yaitu pada pengujian pertama variasi side rake angle 14⁰ pada kedalaman pemotongan 0,5 mm dengan nilai kekasaran permukaan total ketiga spesimen 3,35 µm dan pengujian keempat yaitu dengan variasi side rake angle 16⁰ pada kedalaman pemotongan 0,5 mm dengan nilai kekasaran total 3,47 µm dan nilai kekasaran masing-masing spesimen pada kelas N8.